Meta‐Analysis of Urban Non‐Point Source Pollution From Road and Roof Runoff Across China - Yongxin Wang; Chunlin Li; Jianmin Qiao; Yuanman Hu; Qian Zhang; Jiabo Yin; Louise Slater (Earth's Future)
Abstract Urban non‐point source (NPS) pollution has become an important issue affecting water quality, but current research has focused mainly on local scales and has lacked systematic evaluations at large spatial scales. Here, a meta‐analysis was conducted to explore the characteristics of runoff pollution indicators (TSS: total suspended solids, TN: total nitrogen, TP: total phosphorus, and COD: chemical oxygen demand) on the roads and roofs in 41 Chinese cities, and a boosted regression tree model was used to reveal the geographical differences in pollution levels and the contribution rates of their influencing factors. The results revealed that the average event mean concentrations (EMCs) of TSS (326 mg/L), TP (0.6 mg/L), and COD (160 mg/L) were significantly greater in road runoff than in roof runoff. Among them, the TSS concentrations were nearly four times greater than those in roof runoff, whereas the TP and COD concentrations were 3.2 and 2.3 times greater, respectively. Urban NPS pollution is severe in China, and the concentrations of runoff pollutants far exceed those in the USA, Germany, and France. There were significant geographical differences in urban NPS pollution due to the influences of air quality (35% relative contribution), climate conditions (15%), and human activities (45%). Prominent pollution from road runoff was observed in the Central region, more severe pollution from roof runoff was observed in the Northern region, and relatively light pollution was observed in the Southern and North‐Eastern regions. This study provides the first synthesis of NPS road and roof runoff pollution levels in Chinese cities on a large spatial scale, resulting in scientific guidance for urban stormwater management and NPS pollution control.